Pengembangan Website Yayasan Wangi Bumi Nusantara dalam Diseminasi Informasi Pengelolaan Bank Sampah Kota Depok - Lubis, Kenny Badjora; Fairus, Sirin; Azizi, Aqil (Indonesian Journal for Social Responsibility, 2022)
In order to support the empowerment of the Waste Bank, Bakrie University collaborates with the Wangi Bumi Nusantara Foundation as a partner in charge of 11 District Waste Bank Coordinators in Depok. Partners have played a role as a forum for the Waste Bank network, environmental activists, research and development programs, empowering human resources, and innovating environmentally friendly products. Currently, partners face communication problems to support routine activities and community development, such as recording waste bank transactions, coordination, providing recycled product storefronts, data analysis, branding, and product marketing. Therefore, we need a tool that can overcome those problems. The purpose of this activity is to design, create and fill out content on a prototype web portal. The portal is a combination of a website and a web portal. The website serves to convey information about waste banks for community members. This portal also functions as a showcase for waste bank products. The methodology is carried out through preparation stages, surveys of potential development activities, Focus Group Discussions, technology transfer, website prototyping, ecoprint training with ponding techniques, training on using web portals, evaluation, monitoring, and mentoring. Currently, the web portal is active and can be accessed by partner, waste bank managers, and the general public via https://wangibuminusantara.org which is hosting for the next 3 years. Technology transfer and website management assistance have also been carried out to partner and Coordinators of Sub-District Waste Banks. Partners say this web application is very helpful in introducing profiles, program information and product marketing.